Simulation of Growth and Yield of Rice under Different Agronomic Management and with Changing Climatic Parameters in Central Terai, Nepal - Bastola, A.; Karki, T.; Marahatta, S.; Amgain, L. P. (Journal of the Institute of Agriculture and Animal Science, 2020)
An experiment was conducted in Chitwan, Central Tarai, Nepal in three factorial strip-split plot design to simulate the effect of agronomic management and climate change parameters on growth and yield of rice under two crop establishment methods (transplanted in puddling and direct seeded in zero tillage); two residue retention levels (residue kept at 3 t/ha and no residue); and two nitrogen (N) levels (recommended dose: 100 kg N/ha and farmers dose: 50 kg N/ha) using the variety ‘Ramdhan’ during the rainy season of 2016. Soil of the experiment site was sandy loam and moderately acidic. Decision Support System for Agrotechnology Transfer (DSSAT) ver. 4.6 was used to validate the datasets of field experiment. File-A, File-T, File-W, File-X and Soil file were prepared and genetic coefficient of the variety was determined as P1 (900.00), P2O (70.00), P2R (800.00), P5 (12.60), G1 (99.00), G2 (0.035), G3 (0.02), G4 (0.85) and PHINT (83.0). Crop geometry (row spacing from 20 cm × 20 cm to 15 cm × 15 cm) increased the simulated grain yield from 5406 kg/ha to 5539 kg/ha, and simulated straw yield from 5410 kg/ha to 5797 kg/ha. Either early or late planting from 22 June decreased the simulated grain yield of rice. The increase in temperature by the years 2020, 2050 and 2080 A.D. decreased the simulated grain yield to 4518, 4098 and 2543 kg/ha, respectively, and increase in the level of CO2 concentration and solar radiation can increase the yield slightly with increase in the minimum and maximum temperature’s.